A framework for implementing cloud based enterprise resource planning (ERP) in the transport business sector in Zimbabwe. - Bindi, Maxwel (Midlands State University, 2017)
This study sought to develop a framework for the implementation of cloud based Enterprise Resource Planning (ERP) system in the transport business sector in Zimbabwe: A case of CMED (Pvt) Ltd. Information was gathered through interviews, questionnaire and case study approaches. The concept of cloud computing is not new in the transport business but it was used for telematics only not for integrated system like ERP. An Enterprise Resource Planning (ERP) system is an enterprise-wide software system that provides comprehensive functionality and allows integration of core business processes in organisations. Participants were selected from CMED (Pvt) Ltd different provinces dotted around the country. The results suggested that there is need to develop a framework for the implementation of cloud based ERP system in the transport business sector in Zimbabwe. There was evidence to suggest that top management involvement is key to the successful implementation of cloud based ERP system. Gaining trust and support from top management is very important as they are the once who avails resources for the successful implementation of the cloud based ERP. Data security is also a key issue in the implementation of cloud based ERP system. The proposed framework suggested that there are eight stages: present situation analysis, problem and business process detection, developing new process, information system incorporation, organizing system training, application, process improvement, and ERP system Delivery. There are also issues that must be addressed before moving the data into the cloud. These issues includes individual, corporate, strategic well as security issues. These issue have to be address at every stage for the implementation to be successful. The study recommended that for CMED (Pvt) Ltd to gain competitive advantage, it is vital to give enough time towards training of users, involve users from the beginning of the project, get top management trust and support, and allocate enough resources towards the problem and involved qualified people to be part of the project team to avoid loss of company resources. Cloud based ERP system promotes mobile computing, which is the ability to access resources from anywhere at any time. Future research can look at the storage capacity and cloud data encryption in conjunction with the proposed cloud based ERP implementation framework.